Pertumbuhan Tanaman Sorgum (Sorghum bicolor (L.) Moench) Numbu, BMR Galur G5 dan G8 pada Dosis Pupuk Kandang yang Berbeda di Tanah Podsolik Kalimantan Timur: Growth of Sorghum (Sorghum bicolor (L.) Moench) Numbu, BMR Varieties G5 and G8 at different Doses of Manure in Podzolic soil East Kalimantan - Safitri, Apdila; Daru, Taufan Purwokusumaning; Anjani, Fandini Meilia; Ardiansyah; Huko, Fortunatus Amandus Puji (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
This study aims to determine the growth of several sorghum varieties at different doses of manure in podzolic soil of East Kalimantan. This study used a two-factor experimental design made in a Completely Randomized Design (CRD) with a 3 x 3 factorial pattern using three sorghum varieties (G1: Numbu, G2: BMR G5 line and G3: BMR G8 line), three treatments of manure doses (P0: without manure, P1: 10 tons ha-1, and P2: 20 tons ha-1) with three replications. The variable tested included plant height, stem diameter, leaf length, leaf width and number of leaves. There was an interaction between the use of 10 tons ha-1 manure on the Numbu sorghum variety which had a better effect on sorghum growth including plant height, stem diameter, leaf length and width (p<0.05). There were different results in the number of leaves, the BMR G5 variety without manure was higher than other combinations (p<0.05). The conclusion of this study indicates that fertilizer with a dose of 10 tons ha-1 on sorghum variety Numbu has better growth properties. Key words: fertilization, growth, manure, sorghum varieties